Massive hemorrhages of gastroduodenojejunal origin: Treatment of those originating in peptic ulcerations - Botto, Juvenal; Gateño Yaffe, Nisso; Pino, Juan C; Berriel, Hipólito (Cirugía del Uruguay, 1981)
Study of 75 patients having undergone massive gastroduodenojejunal hemorrhages. 59 cases correspond to peptic ulcerous disease and were treated by subtotaf gastrectomies with a mortality of 7.4 %-